(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The novel virus commonly known as COVID-19epidemic, because of which millions of people infected. The COVID-19pandemic has affected more than 184nations creating a need for implementation of lockdown in towns and cities. This pandemic struck markets globally causing a global recession. On March 23, the Indian Government executed a nation-wide lockdown for battling against the pandemic and irradiate its effects. Because of this move, several businesses were directly hit and many unaccounted employment losses. Also, various transportation and travel industries were critically affected. In view of the situation and in response to the momentary economic adversity, RBI has taken proper steps to eradicate the situation mentioning all loaning societies such as banks and housing finance companies for giving three-month moratorium on term loans, EMI and credit card repayments to their borrowers.Most of them chose adopting this moratorium scheme and implemented this in their loan policies. In this paper we shall know who all shall be benefited because of moratorium and how does it work.